Sex differences in the role of atypical PKC within the basolateral nucleus of the amygdala in a mouse hyperalgesic priming model - Baptista-de-Souza, Daniela; Tavares-Ferreira, Diana; Megat, Salim; Sankaranarayanan, Ishwarya; Shiers, Stephanie; Flores, Christopher M.; Ghosh, Sourav; Luiz Nunes-de-Souza, Ricardo [UNESP]; Canto-de-Souza, Azair [UNESP]; Price, Theodore J. (My University, 2020)
Though sex differences in chronic pain have been consistently described in the literature, their underlying neural mechanisms are poorly understood. Previous work in humans has demonstrated that men and women differentially invoke distinct brain regions and circuits in coping with subjective pain unpleasantness. The goal of the present work was to elucidate the molecular mechanisms in the basolateral nucleus of the amygdala (BLA) that modulate hyperalgesic priming, a pain plasticity model, in males and females. We used plantar incision as the first, priming stimulus and prostaglandin E2 (PGE2) as the second stimulus. We sought to assess whether hyperalgesic priming can be prevented or reversed by pharmacologically manipulating molecular targets in the BLA of male or female mice. We found that administering ZIP, a cell-permeable inhibitor of aPKC, into the BLA attenuated aspects of hyperalgesic priming induced by plantar incision in males and females. However, incision only upregulated PKCζ/PKMζ immunoreactivity in the BLA of male mice, and deficits in hyperalgesic priming were seen only when we restricted our analysis to male Prkcz−/− mice. On the other hand, intra-BLA microinjections of pep2m, a peptide that interferes with the trafficking and function of GluA2-containing AMPA receptors, a downstream target of aPKC, reduced mechanical hypersensitivity after plantar incision and disrupted the development of hyperalgesic priming in both male and female mice. In addition, pep2m treatment reduced facial grimacing and restored aberrant behavioral responses in the sucrose splash test in male and female primed mice. Immunofluorescence results demonstrated upregulation of GluA2 expression in the BLA of male and female primed mice, consistent with pep2m findings. We conclude that, in a model of incision-induced hyperalgesic priming, PKCζ/PKMζ in the BLA is critical for the development of hyperalgesic priming in males, while GluA2 in the BLA is crucial for the expression of both reflexive and affective pain-related behaviors in both male and female mice in this model. Our findings add to a growing body of evidence of sex differences in molecular pain mechanisms in the brain.
Keywords: aPKC; Basolateral amygdala; GluA2; Hyperalgesic priming; Sex differences; ZIP